2021
DOI: 10.3389/fpain.2021.705276
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Migraine Pathophysiology and Treatment: A Review of Current Perspectives

Abstract: Chronic migraine is a disabling neurological disorder that imposes a considerable burden on individual and socioeconomic outcomes. Chronic migraine is defined as headaches occurring on at least 15 days per month with at least eight of these fulfilling the criteria for migraine. Chronic migraine typically evolves from episodic migraine as a result of increasing attack frequency and/or several other risk factors that have been implicated with migraine chronification. Despite this evolution, chronic migraine like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 189 publications
0
36
0
1
Order By: Relevance
“…The hypothalamus is a possible origin of migraine attacks as the trigeminovascular system, innervating the dura mater and of the major brain blood vessels, is activated during the headache phase. 34 , 47 Some studies have suggested that patients with migraine exhibit subtle differences in brain structures related to pain processing or in the trigeminovascular system during the interictal phase. 41 Calcitonin gene‐related peptide (CGRP), abundant in trigeminal ganglion neurons, has an important role in generating migraine headaches.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothalamus is a possible origin of migraine attacks as the trigeminovascular system, innervating the dura mater and of the major brain blood vessels, is activated during the headache phase. 34 , 47 Some studies have suggested that patients with migraine exhibit subtle differences in brain structures related to pain processing or in the trigeminovascular system during the interictal phase. 41 Calcitonin gene‐related peptide (CGRP), abundant in trigeminal ganglion neurons, has an important role in generating migraine headaches.…”
Section: Methodsmentioning
confidence: 99%
“…The hypothalamus is a possible origin of migraine attacks as the trigeminovascular system, innervating the dura mater and of the major brain blood vessels, is activated during the headache phase. 34,47 Some studies have suggested that patients with migraine exhibit subtle differences in brain structures related to pain processing or in the trigeminovascular https://doi.org/10.2147/JPR.S329280…”
Section: Migraine Pathophysiology Is Related To Central Sensitizationmentioning
confidence: 99%
“…Although the pathophysiology of migraine is still, at this date, not completely understood, several recent exhaustive reviews have gathered and explained the multifactorial causes of this neurologic condition [ 78 80 ]. Such causes include genetic, anatomical and physiological (neurovascular) alterations, being the bases for the numerous theories that try to explain the various phases of migraine [ 78 80 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Although the pathophysiology of migraine is still, at this date, not completely understood, several recent exhaustive reviews have gathered and explained the multifactorial causes of this neurologic condition [ 78 80 ]. Such causes include genetic, anatomical and physiological (neurovascular) alterations, being the bases for the numerous theories that try to explain the various phases of migraine [ 78 80 ]. In particular, the neurovascular theory correlates the dura mater vessels innervation by fibres from the trigeminal ganglion and the release of inflammatory neuropeptides, such as the calcitonin gene-related peptide (CGRP) with consequent vasodilation, inflammation and initiation of headache [ 10 ].…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation